Study of influence of structurizing regims on the properties of structural glass-fiber plastics - Karandashov, O. H.; Avramenko, V. L.; Vashchenko, O. V.; Podhornaya, L. F. (Scientific and technological corporation "Institute for single crystals", 2018)
Manufacturing of glass-fiber articles under specified strength characteristics, different ratio of layer thickness to inner diameter and without defects and delaminations is investigated. The influence of technological regimes, degree of curing on the physical and mechanical characteristics of glass-fiber articles was studied. In order to estimate the quality of the obtained articles, and to obtain reliable data on the course of the structuring process, methods of extraction, infrared spectroscopy and differential scanning calorimetry were used.

Досліджено отримання склопластикових виробів з різним співвідношенням товщини стінки та внутрішнього діаметра з заданими міцносними характеристиками без дефектів та розшарувань. Вивчено вплив технологічних режимів, ступеня затвердіння на фізико-механічні характеристики склопластикових виробів. Для оцінки якості цих виробів, отримання надійних даних про хід процесу структурування, в роботі використано методи екстракції, інфрачервоної спектроскопії та диференціальної скануючої калориметрії.
Дослідження впливу технологічних режимів структурування на властивості конструкційних склопластиків
Keywords: study; glass-fiber plastics; physical and mechanical characteristics; differential scanning calorimetry were; infrared spectroscopy; склопластикові вироби; інфрачервона спектроскопія; диференціальна скануюча калориметрія; методи екстракції; фізико-механічні властивості